2017
DOI: 10.1002/solr.201600023
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Control of Ag Polyhedron Nanoparticles for Cost‐Effective and Fast Solar Steam Generation

Abstract: Since introduction of inorganic metallic salt serves as an inducer for modulating crystalline nucleation and overgrowth, we have synthesized highly monodispersed silver nanoparticles (AgNPs) (diameter: 48.7–411.9 nm) in the shape of polyhedral quasi‐spheres via a household microwave oven. The localized surface plasmon resonance (LSPR) absorption spectrum of AgNPs exhibits a good match to the solar spectrum in the UV to near infrared wavelength range. Consequently, AgNPs dispersed in deionized (DI) water have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 71 publications
(153 reference statements)
1
47
0
Order By: Relevance
“…Furthermore, we pulverized some C‐FFNS samples and pass the standard filtration to obtain a freeze‐dried flour powder particle (i.e., called C‐FFP) size of ≈450 μm as dense packed samples. Unlike nanograde sample stacks, these three kinds of macro samples stacking are similar in terms of optical absorption, hydrophilicity, and mechanical strength . We concluded that important factors affecting the evaporation efficiency of these three different stacking materials are their different thermal management.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we pulverized some C‐FFNS samples and pass the standard filtration to obtain a freeze‐dried flour powder particle (i.e., called C‐FFP) size of ≈450 μm as dense packed samples. Unlike nanograde sample stacks, these three kinds of macro samples stacking are similar in terms of optical absorption, hydrophilicity, and mechanical strength . We concluded that important factors affecting the evaporation efficiency of these three different stacking materials are their different thermal management.…”
Section: Resultsmentioning
confidence: 93%
“…Unlike nanograde sample stacks, these three kinds of macro samples stacking are similar in terms of optical absorption, hydrophilicity, and mechanical strength. [50,51] We concluded that important factors affecting the evaporation efficiency of these three different stacking materials are their different thermal management. The mass changes of C-FFNC, C-FFNS, and C-FFP have large differences (Figure 4a).…”
Section: Resultsmentioning
confidence: 94%
“…[163] Its absorption ability has gone beyond that of Ge nanoparticles, [214] BiInSe foam, [164] and Al nanoparticles. [215] Te can combine the features of both LSPR-based absorption [45,47,215,216] and all-dielectric absorption, [214,217] to enhance the absorption. As noted in the scattering spectra (Figure 5b), the plasmonic-like resonance contributes to the main scattering of the Te nanoparticles with size smaller than 120 nm.…”
Section: Tellurenementioning
confidence: 99%
“…Various solar energy harvesting technologies, such as solar cells, artificial photosynthesis, photocatalysis, and solar‐thermal technology, are being developed at present . Among these solar energy harvesting technologies, solar–thermal technology, which converts the absorbed sunlight into thermal energy through photothermal materials, has received considerable attention due to its low cost and high conversion efficiency . This technology has been successfully used in water heaters, water desalination, power generation, and photothermal therapy, but it can still be further developed for other potential applications.…”
Section: Introductionmentioning
confidence: 99%